Contrastive Analysis of Action Verb Phrases in Japanese and ‎Minangkabau: A Syntactic and Semantic Review - Electra Septarani; Dasim Budimansyah‎; Encep Syarief Nurdin‎; Warlim‎; Yelvia Septi Mayenti‎ (Yayasan Darussalam Bengkulu, 2026)
This study investigates the syntactic and semantic similarities and differences between Japanese and Minangkabau action verb phrases, with particular attention to how both languages encode action, agency, aspect, modality, and pragmatic meaning. Employing a qualitative descriptive design, the study analyses action verb phrase data drawn from Chūjōkyū no Nihongo Kyōshitsu kara Tobidasō! and selected Minangkabau texts from jurnalminang.id. The data were examined using a translation-based analytical method, supported by determining-element identification and comparative linking techniques to identify structural correspondences, semantic equivalences, and potential areas of crosslinguistic interference. The findings reveal that Japanese and Minangkabau differ significantly in their typological organisation. Japanese action verb phrases generally follow a head-final and agglutinative pattern, in which grammatical meanings such as progressivity, potentiality, passivity, causation, and unintended consequence are encoded through particles and verbal inflection. In contrast, Minangkabau tends to employ a head-initial and analytic structure, relying on independent lexical markers, aspectual elements, and contextual interpretation to express comparable semantic functions. Despite these structural differences, both languages demonstrate functional equivalence in representing core action-related meanings, including volition, prohibition, politeness, and causality. The study contributes to contrastive linguistics by showing that semantic similarity does not necessarily imply syntactic or morphological equivalence. Pedagogically, the findings provide a foundation for developing Japanese teaching materials that are more responsive to the linguistic background of Minangkabau-speaking learners and may help reduce structural interference in Japanese language acquisition.